Land acquisition act : details on amendments land acquisition act from 1965 to April1987 : all amendments up to 20th April, 1987 = Akta pemerolehan tanah : perihal pindaan-pindaan akta pemerolehan tanah dari 1965 hingga April 1987 : semua pindaan-pindaan hingga 20hb April, 1987 (Kuala Lumpur : MDC, 1987)
28